2022
DOI: 10.1186/s41182-021-00386-0
|View full text |Cite
|
Sign up to set email alerts
|

The 2017 Dengue virus 1 outbreak in northern Vietnam was caused by a locally circulating virus group

Abstract: Background Dengue virus (DENV) is a member of insect vector-borne viruses, and it causes dengue fever. Southeast Asia is the epi-center of dengue fever in the world. The characterization of the virus is essential to identify the transmission and evolution of DENV. Objectives In 2017, there was an outbreak of Dengue virus type 1 (DENV1) in northern Vietnam and the neighboring countries. To identify the genetic character of the outbreak virus in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 18 publications
0
17
0
2
Order By: Relevance
“…To determine whether the current epidemic strains were similar to the strains that were prevalent at T A B L E 1 Relation between primary/secondary dengue infection and DENV genome positivity using real-time PCR in Vung Tau, 2022. and 2017. 8,12,13 In 2019, a large DENV-2 outbreak with closely related strains isolated earlier in Southeast Asian countries was reported in Vietnam. 14 Because the newly identified DENV-2 lineage in this report has not been previously identified in Vietnam, it is worth exploring its origin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether the current epidemic strains were similar to the strains that were prevalent at T A B L E 1 Relation between primary/secondary dengue infection and DENV genome positivity using real-time PCR in Vung Tau, 2022. and 2017. 8,12,13 In 2019, a large DENV-2 outbreak with closely related strains isolated earlier in Southeast Asian countries was reported in Vietnam. 14 Because the newly identified DENV-2 lineage in this report has not been previously identified in Vietnam, it is worth exploring its origin.…”
Section: Resultsmentioning
confidence: 99%
“…We collected 1889 serum samples from patients with suspected dengue and collected information on disease manifestations. Viral RNA was extracted from the specimens using a Qiagen Viral RNA Mini Kit (Qiagen), and real‐time polymerase chain reaction (PCR) was used for DENV testing 8 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These travellers are more likely to visit distant areas and rural regions. Interestingly, the only serotype isolated from travellers returning from Vietnam was DENV-1, which was the predominant serotype during the 2017 outbreak [ 27 ]. DENV-1 was also found in patients returning from the Maldives.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Recently, Takemura et al reported that the dengue outbreak in northern Vietnam in 2017 was caused by a locally circulative viral group. [8] In Thailand, a survey on dengue fever between 2011-2016 revealed that people from 10-14 years old were most vulnerable to the infection, followed by 15-19 years old. Different serotypes had been identified, i. e., DENV-2 in 2012, DENV-3 in 2014, DENV-4, and DENV-3 in 2015.…”
Section: Introductionmentioning
confidence: 99%